Pengaruh Debt To Equity Ratio, Return On Asset Dan Growth Opportunity Terhadap Nilai Perusahaan - Kristina, Kristina; Hasanuh, Nanu (Jurnal Ilmiah Wahana Pendidikan, 2025)
The company’s value reflects investors expectations of potential future profits, as well as the risk associates with investing in the company. This studi aims to empirically examine the effect of Debt to equity ratio (DER), Return on asset (ROA), and Growth opportunity both partially and simultaneously on the value of compaines that use price to book value (PBV) in registered food&beverage companies. On the indonesia stock exchange for the 2019-2021 period. There were 12 samples that met the criteria and 36 observation data. The method used in this research is a quantitative method by taking data from annual financial reports. The hypothesis testing method used in thisa study is the multiple linear regresion analysis method. The result of this study prove that partially there is no effect of the Debt to equity ratio variable on firm value, the Return on assets variable has a positive effect on firm value, and the Growth opportunity variable has a positive effect on firm value.